ON THE AVAILABILITY VERSUS TRANSMITTED POWER OF WIRELESS SENSOR NETWORKS IN RAYLEIGH MULTIPATH FADING ENVIRONMENTS - Milić, Dejan; Anastasov, Jelena; Đošić, Danijel; Seferi, Aldis (Bulletin of Natural Sciences Research, 2017)
This paper presents simulation results for full availability of a wireless sensor network depending on the RF outputpower of the network nodes in Rayleigh multipath fading environment. Outage probability, relating to the situationin which any one of the sensors is unavailable, is computed by means of numerical simulation, and discussed. Theresults indicate that the trade-of between the outage probability and the energy eciency of the network nodes shouldbe sought, resulting in lowest required output power for the highest tolerable outage threshold.